2011
DOI: 10.1292/jvms.10-0350
|View full text |Cite
|
Sign up to set email alerts
|

Epizootiological Study of Tick-Borne Encephalitis Virus Infection in Japan

Abstract: ABSTRACT. Tick-borne encephalitis virus (TBEV) is a zoonotic agent causing severe encephalitis in humans. Rodent species that are potential hosts for TBEV are widely distributed in various regions in Japan. In this study, we carried out large-scale epizootiological surveys in rodents from various areas of Japan. A total of 931 rodent and insectivore sera were collected from field surveys. Rodents seropositive for TBEV were found in Shimane Prefecture in Honshu and in several areas of Hokkaido Prefecture. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 16 publications
(22 reference statements)
2
22
0
Order By: Relevance
“…The only tick-borne viruses known to be endemic in Japan are TBEV and severe fever with thrombocytopenia syndrome virus (SFTSV) (Kentaro et al, 2013;Takahashi et al, 2014;Takashima et al, 1997;Yoshii et al, 2011); the distribution of others has not been investigated. In this study, we collected and tested ticks to investigate the distribution of tick-borne arboviruses in Kyoto, Japan, and isolated Thogoto virus (THOV), which has not previously been reported in far-eastern Asia.…”
mentioning
confidence: 99%
“…The only tick-borne viruses known to be endemic in Japan are TBEV and severe fever with thrombocytopenia syndrome virus (SFTSV) (Kentaro et al, 2013;Takahashi et al, 2014;Takashima et al, 1997;Yoshii et al, 2011); the distribution of others has not been investigated. In this study, we collected and tested ticks to investigate the distribution of tick-borne arboviruses in Kyoto, Japan, and isolated Thogoto virus (THOV), which has not previously been reported in far-eastern Asia.…”
mentioning
confidence: 99%
“…This ratio of isolation was similar to that in a survey conducted in the same area in 1995-1996 (1.2%: 2/169) (Takeda et al 1999). The proportion of rodents 4% in 1995-1996and 10.4% in 2008(Takeda et al 1999, Yoshii et al 2011. These data demonstrated that TBEV has been endemic in wild rodents and ticks in Hokuto.…”
Section: Discussionmentioning
confidence: 70%
“…TBEV was isolated from dogs, ticks, and rodents in the area where the patient with TBE lived (Takeda et al 1998, Takeda et al 1999, and the virus was identified as the Far Eastern subtype of TBEV after nucleotide sequence analysis. Although no TBE case has been reported on Hokkaido since the first case, our epizootiological survey indicated that endemic foci of TBEV were maintained in Hokuto until recently (Yoshii et al 2011). Therefore, isolating and characterizing TBEV endemic in the area is necessary to evaluate the epidemiological risk of TBE.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…During the 20-year gap between cases, serologic and virologic surveys of wild animals ( 5 , 6 ) clarified that TBEV has been maintained in animal populations, especially in wild rodents in Hokkaido. Given the continued ecologic findings of virus activity in animals, it is plausible that humans have acquired TBEV infection, especially persons frequently exposed to ticks, including Japan Self-Defense Forces (JSDF) members of the Northern Army.…”
mentioning
confidence: 99%